Analisis Sistem Informasi Akuntansi Atas Siklus Penggajian Pada PT. Perkebunan Nusantara Satu Regional Delapan di Makassar - Abd. Mursyid; Sitti Hajerah Hasyim; Nur Afiah (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyze the accounting information system for the payroll cycle and determine the level of effectiveness of the payroll cycle at PT Perkebunan Nusantara Satu Regional Delapan. The subjects in this study were the Accounting & Finance Department and the Human Resources (HR) Department which are related to the payroll cycle. Data collection techniques used interviews and documentation. The results show that the payroll system at PTPN implements regular employee data updates before payroll, with a focus on grades that change once a year, and attendance is updated monthly through the SAP application. Employee attendance is recorded through a fingerprint system and submitted to HR for salary recaps, discrepancies in attendance numbers can affect salaries. The payroll process involves the HR department, approval from the Region Head (RH), and verification from the financial accounting department. Automatic salary journaling through Excel and SAP integration produces financial reports, and salary payments are attempted on time, namely every 25th. The payroll system also includes tax deductions and other agreed deductions, as well as PPh 21 calculations that use SAP and are verified manually.